Gluconeogenesis and P-enolpyruvate carboxykinase in liver and kidney of long-term fasted quails - Sartori, DRS; Garofalo, MAR; Roselino, JES; Kettelhut, I. C.; Migliorini, R. H. (Springer, 2000)
The activity of cytoplasmic and mitochondrial phosphoenolpyruvate carboxykinase (PEPCK) in kidney and liver, and in vivo gluconeogenic activity, were determined during different phases of prolonged fasting in quails. The fasting-induced changes in the activity of kidney cytoplasmic PEPCK were positively correlated with the changes in gluconeogenesis. Both activities increased at the initial phase (I) of fasting to levels 65% to 100% higher than fed values, and decreased during the protein-sparing period (phase II), although remaining higher than in fed birds. At the catabolic final phase (III) both kidney cytoplasmic PEPCK activity and gluconeogenesis increased markedly, attaining levels 115% to 150% higher than fed values. The activity of liver cytoplasmic PEPCK, present in appreciable amounts in quails, did not change during phases I and II of fasting, but increased to levels 60% higher than fed values at the final phase (III). Plasma glucose levels at phase III did not differ significantly from those at phases I and II. In both kidney and liver the activity of the mitochondrial PEPCK was not significantly affected by fasting. The data suggest that the kidney cytoplasmic PEPCK is the main enzyme responsible for gluconeogenesis adjustments during food deprivation in quails, and that this function is complemented at the final phase by enzyme present in liver cytosol.
Keywords: phosphoenolpyruvate carboxykinase gluconeogenesis; cytosol; mitochondria kidney; liver